Habitat selection and space use overlap between feral horses, pronghorn, and greater sage‐grouse in cold arid steppe. Issue 1 (4th November 2022) - Hennig, Jacob D.; Scasta, J. D.; Pratt, Aaron C.; Wanner, Caitlyn P.; Beck, Jeffrey L.
Abstract: Populations of feral horses ( Equus ferus caballus ) in the western United States have increased during the past decade, consequently affecting co‐occurring wildlife habitat. Feral horses may influence 2 native wildlife species, greater sage‐grouse ( Centrocercus urophasianus ; sage‐grouse) and pronghorn ( Antilocapra americana ) through mechanisms of habitat alteration and competition. Wyoming, USA, contains the largest populations of pronghorn and sage‐grouse of any state and also has the highest degree of range overlap between feral horses and these species. Consequently, the effects that horses may have on pronghorn and sage‐grouse populations in Wyoming have implications at local, state, and population‐wide levels. Managers need information concerning habitat selection and space use overlap among these species to develop appropriate management strategies; yet this information is absent for most feral horse management areas. To address this knowledge need, we attached global positioning system (GPS) transmitters to horses, pronghorn, and sage‐grouse within the greater Bureau of Land Management–Adobe Town Herd Management Area in southern Wyoming and northern Colorado, USA, between 2017 and 2021 to evaluate habitat selection and space use of all species during 3 biologically relevant seasons: spring (Apr–Jun; sage‐grouse breeding, nesting, and early‐brood rearing; pronghorn late gestation and early parturition), summer (Jul–Oct; sage‐grouse summer and late‐brood rearing; pronghorn late parturition and breeding), and winter (Nov–Mar; non‐breeding season). Feral horses selected flatter slopes and shorter mean shrub height across all seasons and were closer to water in spring and summer. Pronghorn habitat selection was similar to horses, but they also avoided oil and gas well pads year‐round. During spring, sage‐grouse selected greater herbaceous cover, flatter slopes, and areas farther from well pads. In summer, sage‐grouse selected greater mean shrub height, flatter slopes, and were closer to water. In winter, sage‐grouse selected flatter slopes and areas with greater vegetation production during the preceding summer. Our results indicate strong year‐round overlap in space use between horses and pronghorn, whereas overlap between horses and sage‐grouse is greatest during the summer in this region. Consequently, managers should recognize the potential for horses to influence habitat quality of pronghorn and sage‐grouse in the region. Abstract : Feral horses can affect sympatric wildlife through competition and habitat alteration. We examined habitat selection and space use overlap of horses, pronghorn, and greater sage‐grouse in southern Wyoming. Moderate‐to‐strong overlap of high‐use areas by all species indicates potential for horses to negatively influence both pronghorn and sage‐grouse populations in this area.